Refugios militares, Farellones. 2002 (2003)
Refugios de montaña entre dos estaciones de esqui, en los Andes.
Keywords: KLOTZ, MATHIAS; FARELLONES; CHILE; REFUGIOS DE MONTAÑA; ESTRUCTURAS METALICAS; MATERIALES; MADERA